PREVALENCE OF ANXIETY AND DEPRESSION AMONG HOUSEWIVES COMPARED TO WORKING WOMEN IN AGHA BEHJAT MEDICAL CENTER, KARACHI (The Research of Medical Science Review, 2025)
Introduction: Taking anxiety and depression as serious concerns for women, it must be noted that housewives and working women have different difficulties. This paper aims to determine the proportion of housewives and working women having anxiety and depression in Karachi. Objectives: In this study, the researcher aimed to establish the difference between levels of anxiety and depression in housewives and working women. To have insights about probable risk factors that may be affecting the entire population, the authors focused on differences in mental health between two groups. Materials and Methods: A cross-sectional comparative study was conducted in Agha Behjat Medical Center, Karachi from September 2024- February 2025. Three hundred participants of female gender were screened, and their responses to the PHQ-9 and GAD-7 questionnaires led to their classification as housewives or working women. Statistical analysis were done using the Statistical Package Program for Social Science(SPSS). Results: The prevalence of anxiety was higher among housewives, 62.7%, as compared to working women, 45.3% and similarly, the prevalence of depression was 58.7% among housewives as compared to 41.3% among working women. The causes of financial dependence included family status, low levels of education and social isolation. Conclusion: It is highlighted that employment, psychological therapies focused on a particular demographic, financial improvement, and social support should be a priority to support housewives.